2014
DOI: 10.1007/s10162-014-0487-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Cochlear Frequency Selectivity with Stimulus-frequency Otoacoustic Emissions in Chinchillas

Abstract: It has been suggested that the tuning of the cochlear filters can be derived from measures of otoacoustic emissions (OAEs). Two approaches have been proposed to estimate cochlear frequency selectivity using OAEs evoked with a single tone (stimulus-frequency (SF)) OAEs: based on SFOAE group delays (SF-GDs) and on SFOAE suppression tuning curves (SF-STCs). The aim of this study was to evaluate whether either SF-GDs or SF-STCs obtained with low probe levels (30 dB SPL) correlate with more direct measures of cochl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 66 publications
3
14
0
Order By: Relevance
“…Interestingly, stimulus-frequency otoacoustic emissions in chinchillas exhibit frequency dependencies consistent with the existence of basal and apical segments of the cochlea which transition in the 6.5–9 mm region. Their average magnitudes exhibit a conspicuous minimum around 3 kHz (Siegel et al, 2005), whose characteristic place lies in the transition region, and their suppression tuning curves differ drastically for probe frequencies 4 and 12 kHz, which closely resemble ANF tuning curves, vs. 1-kHz probes, which have high-frequency arms that are nearly flat over a 2-octave range, as might be expected from basal emission sources due to reflections at the transition region (Charaziak and Siegel, 2012). …”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, stimulus-frequency otoacoustic emissions in chinchillas exhibit frequency dependencies consistent with the existence of basal and apical segments of the cochlea which transition in the 6.5–9 mm region. Their average magnitudes exhibit a conspicuous minimum around 3 kHz (Siegel et al, 2005), whose characteristic place lies in the transition region, and their suppression tuning curves differ drastically for probe frequencies 4 and 12 kHz, which closely resemble ANF tuning curves, vs. 1-kHz probes, which have high-frequency arms that are nearly flat over a 2-octave range, as might be expected from basal emission sources due to reflections at the transition region (Charaziak and Siegel, 2012). …”
Section: Discussionmentioning
confidence: 90%
“…Most of our methods have been described previously (Charaziak and Siegel, 2014, 2015). Adult chinchillas were anesthetized with ketamine hydrochloride (20 mg/kg, injected subcutaneously), followed by Dial (diallylbarbituric acid) in urethane (initial doses 50 and 200 mg/kg, respectively) with additional doses (20% of the initial one) given as necessary.…”
Section: Methodsmentioning
confidence: 99%
“…In 1980, Kemp et al found that fully suppressed SFOAE suppression tuning curve (STC) matched closely the tone-on-tone total masking PTC, and firstly predicted that SFOAE STCs might be used to evaluate cochlear function objectively [ 19 ]. Since their pioneering work, despite the complexity of SFOAE extraction [ 20 22 ] and uncertainty about the mechanism of SFOAE generation [ 23 25 ], SFOAE STCs are regarded as reflecting the auditory tuning in some laboratory species [ 26 , 27 ] and behavioural tuning in humans [ 28 30 ]. Additionally, the effect of probe level on the tuning of SFOAE STCs and other types of measurement for FS based on SFOAEs (e.g., SFOAE group delays) were observed in many investigations [ 27 29 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since their pioneering work, despite the complexity of SFOAE extraction [ 20 22 ] and uncertainty about the mechanism of SFOAE generation [ 23 25 ], SFOAE STCs are regarded as reflecting the auditory tuning in some laboratory species [ 26 , 27 ] and behavioural tuning in humans [ 28 30 ]. Additionally, the effect of probe level on the tuning of SFOAE STCs and other types of measurement for FS based on SFOAEs (e.g., SFOAE group delays) were observed in many investigations [ 27 29 , 31 ]. Keefe et al measured SFOAE STCs in humans at probe levels of 20–60 dB SPL and reported that the quality factor based on the equivalent rectangular bandwidth ( Q ERB , indicating the tuning sharpness) of SFOAE STCs varied little with probe level changing [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation